RANCANGAN PROSES MANUFAKTUR MESIN PEMOTONG KENTANG STIK BALADO - Agung Setiawan (2021)
In development, technology was created to facilitate human work. In the process of making potato sticks balado, the cutting process is still done manually using simple cutting tools and human power. This is somewhat less effective in terms of time, security, and the resulting capacity. Therefore it is necessary to make a potato sticks balado cutting machine to help the production of potato business. So that this thesis takes the theme "Design of Balado Potato Stick Cutting Machine" which will focus on the manufacturing process of the machine. The machine manufacturing process is based on time, cost, and materials used. From the manufacturing process of this machine, there are several components that are made, where the total time needed to make the potato sticks balado cutting machine is 6.6 hours. The total cost incurred for the manufacture of this machine is Rp 1,732,530.37. The resulting capacity from the test results using a 0.75 HP motor is 122 kg/hour.